Experimental Study on Hydrocarbon Liquids Migration in Double-Porosity Medium Using Digital Image Analysis - Rahman, Norhan Abd; Foong, Loke Kok (IPTEK Journal of Proceedings Series, 2017)
The development activity of the country has played a part in natural disasters and climate change such as earthquake, El-Nino, tsunamis and water pollution have caused negative impact on human health and geo-environment. More complicated problems arise when the subsurface has experienced earthquake vibration, which no doubt influences the migration of hydrocarbon liquid into the groundwater sources. These problems need to be addressed in ensuring sustainable groundwater utilization. This paper aims to study the characteristics of hydrocarbon liquid migration that are important for the remediation cleanup of contaminated groundwater. The danger of reproductive toxic hydrocarbon chemicals has made actual on-site study infeasible and has been more practically replaced by physical model simulations. For this purpose, a physical laboratory experimental study was conducted to investigate the pattern and characteristics of different quantity toluene hydrocarbon migration in double-porosity medium under the vibration effect by using digital image analysis. The results of the experiments show that lower quantity of toluene hydrocarbon will take longer time to migrate to the bottom compared to higher quantity of toluene hydrocarbon. During experiment, air bubbles were continuously observed at the soil surface of toluene reducing due to the wettability of the liquids in the soil sample and the air trapped between the fractured aggregate and intra-inter aggregate pores. This study indicate that the digital image analysis is capable to provide the hydrocarbon flow rate and useful information for researchers and professionals to comprehensively understand migration characteristic.